Nanotechnology based advanced therapeutic strategies for targeting interleukins in chronic respiratory diseases. (1st October 2021) - Hussain, Md Sadique; Sharma, Parvarish; Dhanjal, Daljeet Singh; Khurana, Navneet; Vyas, Manish; Sharma, Neha; Mehta, Meenu; Tambuwala, Murtaza M.; Satija, Saurabh; Sohal, Sukhwinder Singh; Oliver, Brian.G.G.; Sharma, Hari S.
Abstract: Both communicable and non-communicable chronic respiratory conditions have accorded for suffering of millions of people of all ages and stated to be leading cause of death, morbidity, economic and social pressures, and disability-adjusted life-years (DALYs) worldwide. These illnesses impair patient's health and negatively impacts families and society, particularly in low and middle-income countries. Chronic respiratory diseases (CRDs) affect different organs of respiratory system, involving airways, parenchyma, and pulmonary vasculature. As the number of respiratory diseases are exponentially escalating but still the stakeholders are not paying attention towards its serious complications. Currently, the treatment being used primarily focusses only on alleviating symptoms of these illness rather delivering the therapeutic agent at target site for optimal care and/or prevention. Lately, extensive research is being conducted on airways and systemic inflammation, oxidative stress, airway, or parenchymal rehabilitation. From which macrophages, neutrophils, and T cells, as well as structural cells as fibroblasts, epithelial, endothelial, and smooth muscle cells have been found to be active participants that are involved in these chronic respiratory diseases. The pathogenesis of all these chronic respiratory diseases gets caused differently via mediators and proteins, including cytokines, chemokines, growth factors and oxidants. Presently, the target of prescription therapies is to reduce the inflammation of airways and relieve the airway contraction. In all studies, cytokines have been found to play an imperative role in fostering chronic airway inflammation and remodelling. Owing to the limitations of conventional treatments, the current review aims to summarize the current knowledge about the chronic respiratory disease and discuss further about the various conventional methods that can be used for treating this ailment. Additionally, it also highlights and discusses about the advanced drug delivery system that are being used for targeting the interleukins for the treatment of CRDs. Highlights: Nanotechnology provides novel strategies in clinical treatment of respiratory disorders. Airway defenses is strengthened by sustained release of drugs. Nanocarriers can also be used for combination treatment of drugs targeting interleukins.